Lack of Adolescent Interest in Education in Pinjauan Tinggi Village - Reno Suri Yenti (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2020)
This study aims to find out: 1) internal factors that influence the lack of interest in adolescents in education in the village of Pinjauan Tinggi. 2) External factors that influence the lack of interest in adolescents in education in the village of Pinjauan Tinggi. This research uses a qualitative approach. Data collection techniques used in this study were interviews and observation. Data analysis was performed using an interactive analysis model. The data validity technique uses data and source triangulation techniques. The result showed that: 1) internal factors that influence are: (a) lack of motivation of adolescents to continue their education, (b) choosing migrants looking for work, 2) external factors that influence: (a) Parents income, (b) school environmental, (c) community environmental factors.Keywords: Interest, Education Youth, Internal Factors, External Factors